Internalisasi Nilai-Nilai Multikulturalisme dalam Pembelajaran PAI di Sekolah Dasar Taman Harapan - Syamsul Bahri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: Pendidikan Agama Islam (PAI) is a subject in the national curriculum which is apt to internalize the values of multiculturalism. Nevertheless, in the past decade PAI has not fully implementeda multiculturalism-basedlearning. The research was conducted at Taman Harapan Elementary School in the city of Malang, a private school that has multi-ethnic and multi-religiousstudents. Problem raised in this study is how to internalize the values of multiculturalism into PAI learning in elementary school? Researchers collected the data through observation, interviews and review documents. The results showed that Taman Harapan Elementary School strongly supports the implementation of the internalization of the values of multiculturalism in the school. PAI learning at Taman Harapan Elementary School has implemented internalization of multiculturalism values to students by placing them in the learning curriculum, namely the Competency Standards, Competency and Learning Achievement Indicators. The values of multiculturalism that are integrated into the PAI learning are tolerance, equality, and cooperation.Keywords: Internalization, multiculturalism, PAI, Taman Harapan Elementary School